2011
DOI: 10.1021/ja203979j
|View full text |Cite
|
Sign up to set email alerts
|

The A53T Mutation is Key in Defining the Differences in the Aggregation Kinetics of Human and Mouse α-Synuclein

Abstract: Despite a 95% sequence similarity, the aggregation of human and mouse α-synuclein is remarkably different, as the human form is slower than the mouse form in forming fibrils, but is associated with Parkinson’s disease both in humans and transgenic mice. Here, the amino acid code underlying these differences is investigated by comparing the lag times, growth rates and secondary structure propensities of a systematic series of eight human-mouse chimeras. Fluorescence analysis of the human-mouse variants shows th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
67
3

Year Published

2012
2012
2016
2016

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 51 publications
(78 citation statements)
references
References 33 publications
(57 reference statements)
7
67
3
Order By: Relevance
“…The highly similar morphology of the three samples indicates high reproducibility of our sample preparation, which is an essential requirement if different labeling schemes are to be used for ssNMR. However, both straight and helically twisted fibrils of mAS were observed by EM in the recent study by Kang et al 40 The observed differences of the mAS fibril morphology might be due to different fibrillization conditions and suggests the existence of two types of mAS fibrils (straight and twisted). In the case of hAS fibrils, the overall morphology was demonstrated to be strongly dependent on the fibrillization conditions, and both straight and twisted fibrils were observed and characterized.…”
Section: Resultsmentioning
confidence: 87%
See 2 more Smart Citations
“…The highly similar morphology of the three samples indicates high reproducibility of our sample preparation, which is an essential requirement if different labeling schemes are to be used for ssNMR. However, both straight and helically twisted fibrils of mAS were observed by EM in the recent study by Kang et al 40 The observed differences of the mAS fibril morphology might be due to different fibrillization conditions and suggests the existence of two types of mAS fibrils (straight and twisted). In the case of hAS fibrils, the overall morphology was demonstrated to be strongly dependent on the fibrillization conditions, and both straight and twisted fibrils were observed and characterized.…”
Section: Resultsmentioning
confidence: 87%
“…9,40 mAS aggregates about twice faster, and the lag phase is reduced by almost 1 order of magnitude. 40 To characterize the structural differences between mAS and hAS fibrils at the atomic level, we recorded a set of high-resolution ssNMR spectra on mAS fibrils and compared it to existing data for hAS fibrils that were prepared under identical conditions. 46 As an example, Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Substitution of the human sequence at either position 53 or 87 with the native mouse residue accelerates fibrillization rates substantially (Kang et al, 2011). Likewise, assembly rates for human-mouse chimeric α-Syn proteins fall between that of the two wildtype (wt) proteins and are proportional to their homology to wt mouse (Ms wt α-Syn).…”
Section: Introductionmentioning
confidence: 99%
“…This latter effect is caused by modification of any of the Lys residues causing small chemical shift changes throughout the protein, analogous to what is observed upon mutating a residue. [20] …”
mentioning
confidence: 99%